Adipocyte purinergic receptors activated by uracil nucleotides as obesity and type 2 diabetes targets. (April 2022) - Jain, Shanu; Jacobson, Kenneth A.
Abstract: Extracellular uridine nucleotides regulate physiological and pathophysiological metabolic processes through the activation of P2Y2, P2Y4, P2Y6 and P2Y14 purinergic receptors, which play a key role in adipogenesis, glucose uptake, lipolysis and adipokine secretion. Using adipocyte-specific knockout mouse models, it has been demonstrated that lack of the P2Y6 R or P2Y14 R can protect against diet-induced obesity and improve whole-body glucose metabolism. The P2Y2 R facilitated adipogenesis and inflammation, and the loss of P2Y4 R or P2Y14 R raised the levels of the protective endocrine factor adiponectin. Hence, potent antagonists for these receptors may be tested to identify drug candidates for the treatment of obesity and type 2 diabetes. However, future studies are required to provide insight into purinergic regulation of brown adipocytes and their role in thermogenesis. This review summarizes the current studies on uridine nucleotide-activated P2YRs and their role in adipocyte function, diet-induced obesity and associated metabolic deficits.